Vowel elision and the morphophonology of dominance in Aymara - Kim, Yuni (Onomázein, 2016)
This paper examines morphologically conditioned vowel elision processes in Aymara, and proposes that they are due to a two-way division in Aymara suffixes between those which delete a mora from the preceding morpheme and those which do not. This “dominant/recessive” morpheme analysis builds on and simplifies previous accounts, which specified a preference for consonantal or vocalic environment on both sides of each suffix. I observe some phonological tendencies within suffix categories and propose a diachronic hypothesis as to how morphological vowel elision could have evolved from purely phonological vowel weakening processes that are still found in the language today.